HOW BOLSA FAMÍLIA PROGRAM IMPACTS ON BASIC EDUCATION? AN ANALYSIS FOR THE BRAZILIAN NORTHEAST. - Gomes Neto, Arcenor; Santos, Anderson Moreira Aristides dos; Molnar Prates, Thierry (Revista Econômica do Nordeste, 2020)
This paper aims to investigate the Bolsa Família Program impacts on educational indicators, as enrollment rate and age-grade gap, in the Northeast region and its respective states and mesoregions, for children and teenagers from 6 to 17 years old, using as source the 2010 Census. The Propensity Score Matching method was used for estimation, and complementary tools and sensitivity analysis were applied. The study differentiation is the Northeast states and their respective mesoregions estimation, in a more disaggregated way, since the literature focuses mainly on general analysis. The results indicated a significant impact of PBF on the enrollment rate, and it remains on robustness analysis. However, for the age-grade gap, in general, the impacts were not significant and/or not robust. Also, the observed effect is greater for individuals aged from 15 to 17 years, although in this age range, the program has greater heterogeneity among mesoregions, with non-significant impact cases even for enrollment rate. Thus, is observed the importance of PBF as an incentive, though there are challenges mainly for this older group, and educational policies may be important for improvement of these indicators.